1967
DOI: 10.1021/ja00986a015
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and isotopic study of the decomposition of monoperoxyphthalic acid

Abstract: The mechanism of the decomposition of monoperoxyphthalic acid has been investigated. The rate law is analogous to those found for other monosubstituted peroxides (second order in peroxide with a maximum rate at pH equal to pK* of peroxidic proton). The isotope data are consistent with previously observed cases in that the data are explicable in terms of two competing transition states of identical composition but different configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…The solution pH was measured using a pH meter (PHSe3C, Shanghai Precision Scientific Instrument Co., Ltd.). The concentrations of H 2 O 2 , HSO À 5 , and S 2 O 2À 8 were measured by the iodometric method (Ovenston and Rees, 1950;Ball et al, 1967;Frigerio, 1963). The concentration of natural organic matters (mgC L À1 ) was measured with a Multi 3100 N/C TOC analyzer (Shimadzu), according to ISO-8245 (ISO-8245-1, 1999), and the UV absorbance and absorption spectra were measured with a UV/Vis spectrophotometry (Hatch-DR5000).…”
Section: Methodsmentioning
confidence: 99%
“…The solution pH was measured using a pH meter (PHSe3C, Shanghai Precision Scientific Instrument Co., Ltd.). The concentrations of H 2 O 2 , HSO À 5 , and S 2 O 2À 8 were measured by the iodometric method (Ovenston and Rees, 1950;Ball et al, 1967;Frigerio, 1963). The concentration of natural organic matters (mgC L À1 ) was measured with a Multi 3100 N/C TOC analyzer (Shimadzu), according to ISO-8245 (ISO-8245-1, 1999), and the UV absorbance and absorption spectra were measured with a UV/Vis spectrophotometry (Hatch-DR5000).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, SPB and TBBC are two precursors to the formation of a strongly oxidizing peracid via perhydrolysis. A competing reaction is hydrolysis of TBBC (Lee et al 2010), and base-catalyzed decomposition of peracid (Everett and Minkoff 1953; Goodman et al 1962;Koubek et al 1963;Ball et al 1967), as shown in Fig. 7.…”
Section: Sorption Isothermmentioning
confidence: 99%
“…The iodometric titration method is based on oxidation of KI by PMS or persulfate to liberate iodine and a subsequent back titration with thiosulfate using a starch indicator . This conventional method is tedious, time consuming, and poorly sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The iodometric titration method is based on oxidation of KI by PMS or persulfate to liberate iodine and a subsequent back titration with thiosulfate using a starch indicator. [16,17] This conventional method is tedious, time consuming, and poorly sensitive. Detection of PMS and persulfate using spectrophotometric methods is less time consuming, as these are based on oxidative decolourization of dyes by Fe 2+ or heat-activated persulfate [18,19] and cobalt-activated PMS.…”
mentioning
confidence: 99%